Nulidad e Inexistencia de los Actos Jurídicos en el Derecho Ecuatoriano - César Coronel Jones; Oscar Del Brutto Andrade (Universidad Hemisferios, 2010)
Inexistence and nullity of juridical acts are basic institutions in Ecuadorian Law. These are two different categories that have in common the chasing of the invalidity of the juridical acts that didn’t form according to Law. Inexistent acts are deprived by the law of any legal effect, while null acts have legal effects but a judge can declare them null and erase their legal effects that have already taken place. This paper reviews the legal regulation of inexistent and nullity under Ecuadorian Law, as well as the rulings of the National Court of Justice regarding the issue.